Criminal liability for causing harm to health during sports - Mariia Korabel; Yurii Shynkarov; Alina Plotnikova; Yurii Kuryliuk; Oleksandr Motlyakh (Universidad de Murcia, 2022)
Article accepted. The article will be published here soon. Pending final quality checks.